Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1038/s41598-020-59284-w
|View full text |Cite
|
Sign up to set email alerts
|

The Adipocyte Acquires a Fibroblast-Like Transcriptional Signature in Response to a High Fat Diet

Abstract: Visceral white adipose tissue (vWAT) expands and undergoes extensive remodeling during diet-induced obesity. Much is known about the contribution of various stromal vascular cells to the remodeling process, but less is known of the changes that occur within the adipocyte as it becomes progressively dysfunctional. Here, we performed a transcriptome analysis of isolated vWAT adipocytes to assess global pathway changes occurring in response to a chronic high fat diet (HFD). The data demonstrate that the adipocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 80 publications
(83 reference statements)
5
76
0
Order By: Relevance
“…These chemokines include tumor necrosis factor-alpha (TNFα), inducible nitric oxide synthase (iNOS), interleukin 6 (IL-6), interleukin 8 (IL-8), C-reactive protein, Transforming growth factor beta 1 (TGFβ1), soluble intercellular adhesion molecule (ICAM), and monocyte chemoattractant protein 1 (MCP-1) [31][32][33][34][35][36][37][38][39][40]. Additionally, adipocytes exhibit increased gene expression for ECM production under a high fat diet [41]. Similar to mature adipocytes, adipose derived stem cells (ASCs) also undergo significant changes during obesity.…”
Section: Mechanismsmentioning
confidence: 99%
“…These chemokines include tumor necrosis factor-alpha (TNFα), inducible nitric oxide synthase (iNOS), interleukin 6 (IL-6), interleukin 8 (IL-8), C-reactive protein, Transforming growth factor beta 1 (TGFβ1), soluble intercellular adhesion molecule (ICAM), and monocyte chemoattractant protein 1 (MCP-1) [31][32][33][34][35][36][37][38][39][40]. Additionally, adipocytes exhibit increased gene expression for ECM production under a high fat diet [41]. Similar to mature adipocytes, adipose derived stem cells (ASCs) also undergo significant changes during obesity.…”
Section: Mechanismsmentioning
confidence: 99%
“…In order to understand the processes associated with these changes in obesity, Jones et al evaluated the transcriptional response of adipocytes to a high-fat diet. The authors showed a profibrotic transcriptional reprogramming with upregulation of TGF-ß and Wnt signaling, as well as extracellular matrix–associated genes suggesting that adipocytes potentially transdifferentiate by AMT under these conditions [ 42 •].…”
Section: Amt and Relevance To Disease: What Have We Learnedmentioning
confidence: 99%
“…Obesity is the most commonly encountered disorder of adipose tissue and has been shown to lead to a variety of deleterious outcomes including diabetes, hypercholesterolemia, cardiovascular disease and the metabolic syndrome, and adipose tissue fibrosis. Unlike healthy adipose tissue, adipocytes from obese individuals are under significant metabolic stress which leads them to an abnormal phenotype with features shared with AMT [ 42 •]. Adipose stress is recognized to be present in a number of inflammatory, fibrotic, and neoplastic processes, and likely contribute to the role of AMT in these diseases.…”
Section: Some Significant Unanswered Questions and Future Directionsmentioning
confidence: 99%
“…Body mass index vs. Igf2bp2 levels in visceral 76 (black) or subcutaneous 77 (gray) adipose tissue from 63 individuals shown in (d). Relative lncRAP2 and Igf2bp2 expression in mice 78 (visceral fat, left) or lean/overweight humans 79 (subcutaneous fat, right) fed a high fat diet shown in (e).…”
Section: Resultsmentioning
confidence: 99%